Cultural Isolation and Identification of Possible Causative Agents of Swollen Head Syndrome in Broilers - Momin, Sohilabbas G.; Ghodasara, Dinesh J.; Mathakiya, Rafiuddin A.; Dave, Chandrakant J.; Jani, Purnima B.; Kabariya, Digjay V.; Choudhari, Pradhnya (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present study was conducted for isolation and identification of possible causative agents from broiler birds affected with swollen head syndrome in and around Anand, Gujarat. During six months of study period, a total 40 swab samples were collected from 20 different commercial broiler farms affected with swollen head syndrome. All the twenty broiler flocks under the study were found positive for the presence of Escherichia coli. During the study, overall total of 83 different bacterial isolates were obtained from 20 affected broiler flocks. The isolates included Escherichia coli (34.94%), Staphylococcus aureus (32.53%), Proteus spp. (6.02%), Corynebacterium spp. (7.23%) and Gram negative rods (19.28%). Escherichia coli was found to be the highest prevalent pathogen in swollen head syndrome during the study.